Outcome of Pushback Stenting and ESWL Versus in Situ ESWL for Upper Ureteric Stone -A Comparative Study (KYAMC Journal, 2017)
Background: Urolithiasis is one of the most prevalent urological disorders and the prevalence of urinary stones has increased world wide1. The management of urinary calculi was revolutionized by the introduction of extracorporeal shockwave lithotripsy (ESWL) in 1980 and the first successful ESWL treatment was accomplished in Germany by Dr. Christian Chaussy using a Dornier HM1 lithotripter. ESWL is a safe, effective and non-invasive method2.Purpose: To observe the outcome of pushback stenting and ESWL versus in situ ESWL for upper ureteric stone.Materials and methods: It was a quasi-experimental study. The study was under went in the department of urology, Dhaka Medical College and Hospital, between July'2012 to June'2014. Total 60 patients of single upper ureteric stone who satisfy inclusion and exclusion criteria were enrolled in this study. Selected patients were dived into two groups, group A and group B. Group-A for pushback stenting and ESWL and group-B for in situ ESWL. Results were compared in terms of clearance rates, number of shock waves, sessions, incidence of complications and failure rate.Results: Failure of ESWL was significantly higher in Group B (23.33%) than Group A (10%). These results were statistically significant.Conclusion: Pushback stenting and ESWL is better than in situ ESWL for upper ureteric stone.KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 4-9